The Impact of Entrepreneurial Lifestyle on Business Success: A Systematic Literature Review - Cahyani, Rusnandari Retno; Riani, Asri Laksmi; Harsono, Mugi; Sunaryo, Sinto (Journal of Ecohumanism, 2024)
This study presents a systematic review and bibliometric analysis of the literature exploring the relationship between entrepreneurial lifestyle and business success. Using data collected from Scopus via Harzing's Publish or Perish and analysed with VOSviewer, this research identifies key elements of the entrepreneurial lifestyle that significantly impact business growth and entrepreneurs' satisfaction. These elements include time management, work-life balance, mental health, and technology adoption. The findings show that effective stress management and technology adoption play critical roles in supporting innovation, business sustainability, and preventing burnout that can hinder productivity. The bibliometric analysis also reveals that the related research is still concentrated in certain sectors, such as tourism, with significant geographical limitations. Therefore, this study suggests further exploration across various industry sectors and broader geographical contexts to gain a more comprehensive understanding. The main contribution of this research is to provide practical guidance for entrepreneurs to optimize their lifestyles and to offer insights into existing research trends and patterns through bibliometric analysis.